A Systematic Qualitative Review of Teachers' Strategies in Enhancing Mathematical Reasoning in Elementary Schools - Nurtamam, Mohammad Edy; Jannah, Ana Naimatul (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Mathematical reasoning skills are a fundamental aspect in mathematics learning that contributes to students' conceptual understanding and problem-solving. This study aims to identify and analyze the strategies applied by teachers in improving students' mathematical reasoning skills in elementary schools. The research method used is a qualitative review based on literature studies and data analysis from relevant previous research. The results showed that teachers applied various strategies, including problem-based learning (PBL), group discussions, scaffolding, and the use of technology and interactive media in the learning process. In addition, metacognitive and reflective approaches have proven to be effective in improving students' critical and analytical thinking skills. These findings provide insight for educators in developing more effective teaching methods to improve students' mathematical reasoning.